Vibration-based degradation effect in rechargeable lithium ion batteries having different cathode materials for railway vehicle application. (June 2021) - Lee, Pyeong-Yeon; Park, Seongyun; Cho, Inho; Kim, Jonghoon
Highlights: The performance of a railway vehicle battery under vibration was investigated. Three types of batteries were evaluated through vibration test of railway vehicle. The capacity, resistance, and IC curve were extracted as degradation indicators. Robust optimal battery is selected for vibration of railway vehicles. Abstract: The performance of lithium-ion battery (LIB) has been studied under various conditions of temperature and load depending on the automotive application, since LIB is dominant in cathode active materials. However, majority of those studies are restricted to automotive applications for investigation of its performance. It is necessary to experiment with the impact of vibration and shock since railway vehicles are exposed to complex vibrations by components, railway conditions, and driving profiles. Because of these complex vibration conditions, the battery can be rapidly degraded along with the battery cycles. Thus, it is important to ensure that the actual battery life can be estimated. In this study, the effect of vibration on the LIB was analyzed. The batteries using three types of cathode active materials were observed in terms of electrical performance through electrical characterization tests. The degradation effects by complex vibrations were analyzed by monitoring its resistance, capacity, and incremental capacity. As a result, a battery with high durability was selected among LIBs with different active materials.